Eficiência de compostos de resíduos orgânicos no crescimento de espécies arbóreas - Chiarelotto, Maico (2015)
The accelerated growth of the population caused, among other problems, the pressure for natural resources for the production of consumer goods and the increase on the generation of solid residues worldwide. Facing this situation, the best alternative to solve this problem is to promote the correct management of the residues, considered wrongly as unserviceable, standing out the importance of the treatment stage, that is capable of reinsert them in the production line, reducing the demand for raw material. Considering that a large portion of the residues generated in Brazil consists of organic matter, the composting treatment technique gained extremely importance, since it produces a stabilized compound, capable of use as substrate for the production of seedlings. In this context, this paper aims to treat three types of organic residues, sludge from sewage treatment plant and the tree pruning from urban tree maintenance, both from the county of Francisco Beltrão - PR, and to use the stabilized material in the production of two tree species, Piptadenia gonoacantha (Mart.) J. F. Macbr and Parapiptadenia rigida (Benth.) Brenan. The composting, conducted in the experimental area of UTFPR-FB, was monitored through pH parameters, water content, temperature, volatile solids content. After treatment, the compounds were evaluated as well as the potential for the production of seedlings of the species already mentioned. For this production, were used three treatments, Sc: commercial substrate, Le: 50 % of commercial substrate and 50 % of the compound produced with sewage sludge and Ru: 50% of commercial substrate and 50% of the compound produced using the waste from the University Restaurant. For the monitoring of the seedlings, it was found the phytomorphologic characteristics, root length (CR), shoot length (CA), stem diameter (DC), root dry mass (MR), dry mass of shoots (MA) and number of leaves (NF). Checking the average value of all Phytomorphologics parameters analyzed, we are able to observe that for Parapiptadenia rigida species, the treatment Le and Ru, shows better development in the CA parameter to 30 days after planting. For the rest of the parameters the development of the species in the three treatments was statistically the same. It is observed that for species Piptadenia gonoacantha,the treatment Le showed better development compared to the Sc and Ru treatments. We were able to concluded that in the treatment Le species showed better development compared with other treatments.